2013
DOI: 10.1186/1471-2261-13-93
|View full text |Cite
|
Sign up to set email alerts
|

Association between winter season and risk of death from cardiovascular diseases: a study in more than half a million inpatients in Beijing, China

Abstract: BackgroundSeasonal associations of cardiovascular mortality have been noted in most populations of European origin years ago, but are not well evaluated in Asian populations recently.MethodsUtilizing the electronic Hospitalization Summary Reports (HSRs) from 32 top-ranked hospitals in Beijing, China, we evaluated the association between winter season and the risk of cardiovascular death among hospitalized individuals. General additive models and logistic regression models were adjusted for confounding factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 30 publications
2
17
0
6
Order By: Relevance
“…However, it is still not well recognised if there is any relationship between seasonal variation of 25(OH)D levels and the incidence of acute myocardial infarction (AMI) [4]. These associations might explain the observed relationship between the seasonal periodicity of cardiovascular mortality with a winter peak and summer nadir [12,13].…”
Section: Introductionmentioning
confidence: 95%
“…However, it is still not well recognised if there is any relationship between seasonal variation of 25(OH)D levels and the incidence of acute myocardial infarction (AMI) [4]. These associations might explain the observed relationship between the seasonal periodicity of cardiovascular mortality with a winter peak and summer nadir [12,13].…”
Section: Introductionmentioning
confidence: 95%
“…In some other studies, in addition to the abovementioned effective factors, geographic regions, seasons, and also different hours of a day were recognized as the risk factors. Different statistics regarding death prevalence in many countries and cities in different seasons and hours also confirmed this issue (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 65%
“…Also, in the studies by Heyer and Kloner, MI was more in the warm season (16,21), but in most of the studies, MI was observed in winter. Xu et al, in a study conducted in China reported that 30% to 50% of MIs occurred in winter (12); the studies by Spencer in America (19), Daei in Qazvin, Iran (13), Jahanbakhsh in Ahar, Iran, (7) and Oranto et al, (29) also indicated that MI mostly occurred in winter. Marchant et al, believed that ambient temperature had an important role in the acute MI pathogenesis (11).…”
Section: Discussionmentioning
confidence: 99%
“…Эта тенденция подтверждена в исследованиях от-дельных стран, например, в Норвегии и Ирландии ян-варь также оказался месяцем с самой большой смерт-ностью в течение года, и при анализе за 10-летний пе-риод показано, что смертность в январе выше, чем смертность в июле в среднем на 22% и 35%, соответ-ственно [17]. При анализе госпитальной летальности в Китае показано, что пожилые пациенты, госпитализи-рованные в зимние месяцы (ноябрь-февраль) харак-теризовались повышенным риском смерти на 30-50% по сравнению с теми, кого госпитализировали в мае [18].…”
Section: Discussionunclassified